El sistema de Gutiérrez (1841-1853). Administrativización militar, gobierno paternal y faccionalización - Gabriela Tío Vallejo (Nuevo mundo - Mundos Nuevos, 2023)
This article on the government of Celedonio Gutiérrez intends, from the case of Tucumán, to reflect on the construction of provincial leadership during the hegemony of Rosas. To analyze the mechanisms that forged governability between 1841 and 1853, we distinguish three features of his government: military administrativization, paternal government, and factionalism coupled with a unanimista liturgy. The first two features show the persistence of the jurisdictional culture in a context of factional tensions and changing constellations of provincial alliances that characterize the 1840s. The network of military loyalties that sustain and manage the power of the governor, the kinship ties and pseudo-kinship, friendship and subordination within it and the broad powers of these agents. Domestic governance is also studied from the construction of the figure of the father, judge and governor through the extraordinary powers in its aspects of intervention in family matters and summary justice.